Ndaba Ntsele : entrepreneurial vision - Beswick, Claire; Ncube, Mthuli, 1963- ([London] : SAGE, 2016)
Ndaba Ntsele is CEO of Pamodzi Investment Holdings (PIH), a diversified investment company with interests in technology, food and beverage, diversified services, resources and financial services. This text examines Ntsele's career, which spans a broad range of commercial activities.
Originally Published in: Beswick, C., & Ncube, M. (2010). Ndaba Ntsele: Entrepreneurial Vision. WBS-2010-12 Johannesburg: The Case Centre, Wits Business School.
Description based on online resource; title from home page (viewed on April 27, 2016).
Keywords: elektronické knihy; electronic books; Ntsele, Ndaba; Pamodzi Aviation (Firm); New business enterprises -- Case studies